2005
DOI: 10.1111/j.1365-4632.2005.02045.x
|View full text |Cite
|
Sign up to set email alerts
|

Pigmented purpuric dermatosis and hepatitis profile: a report on 10 patients

Abstract: Hepatitis C and B virus may play a role in the pathogenesis of pigmented purpuric dermatosis. Further case-control studies are necessary to confirm this conclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
0
5
2
Order By: Relevance
“…In a report by Dessoukey et al, they proposed that the hepatitis virus may directly induce lymphocytic capillaritis through humoral or cell-mediated immune vessel reaction. 9 In our study, fibrinogen deposition was observed in six out of the seven patients with hepatitis infection; however, no statistically significant association was found between hepatitis infection and fibrinogen deposition. These findings suggest that hypertension, diabetes mellitus, and hepatitis infection may play a role in the development of fibrinogen deposition, inflammation, and red blood cell extravasation observed in PPD.…”
Section: Vascular Iga and Fibrinogen Deposition In Dif Usually Indica...contrasting
confidence: 69%
See 1 more Smart Citation
“…In a report by Dessoukey et al, they proposed that the hepatitis virus may directly induce lymphocytic capillaritis through humoral or cell-mediated immune vessel reaction. 9 In our study, fibrinogen deposition was observed in six out of the seven patients with hepatitis infection; however, no statistically significant association was found between hepatitis infection and fibrinogen deposition. These findings suggest that hypertension, diabetes mellitus, and hepatitis infection may play a role in the development of fibrinogen deposition, inflammation, and red blood cell extravasation observed in PPD.…”
Section: Vascular Iga and Fibrinogen Deposition In Dif Usually Indica...contrasting
confidence: 69%
“…However, it has been linked to vascular problems such as venous hypertension, capillary fragility, stasis dermatitis, physical activity, and infections. [1][2][3][4]9 In this study, the most common deposition was fibrinogen, observed in 71% of patients. Fibrinogen is an acute-phase protein produced by the liver following bacterial infections, trauma, major surgeries, and chronic inflammatory diseases.…”
Section: Vascular Iga and Fibrinogen Deposition In Dif Usually Indica...mentioning
confidence: 47%
“…The etiology of PPD is still much unknown, but venous hypertension, gravitational dependency, exercise, capillary fragility, alcohol ingestion, and focal infection were reported as highly likely to be potential causal or aggravating factors in PPD 7 8 9 10 . Some drugs had been suspected to occur with PPD, such as acetaminophen, aspirin, adalin, glipizide and hydralazine 11 12 13 14 15 16 17 18 19 20 21 22 . In fact, 48.3% of the subjects in this study had concomitant disease such as hypertension, diabetes mellitus, hyperlipidemia and cerebral infarction, but none of them reported that their medication was changed or started at the onset of the symptom.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have suggested an association between PPD and hepatitis B or C infection 4 . While 5 patients were positive for HCV and 2 for HBsAg in a study involving 10 patients, in a case-control study, no statistically significant difference was observed in the prevalence of positive hepatitis B or C serological findings between the patients and controls 2 , 4 . In the present study, only 1 patient was positive for HBsAg and 1, for HCV.…”
Section: Discussionmentioning
confidence: 99%
“…There are very few clinical and etiological studies on PPD in the literature, as the disorder is rather uncommon 2 , 3 . A few case series on the relation between PPD and hepatitis B or C virus and hyperlipidemia have been reported 4 , 5 . PPD patients underwent patch testing only in 1 study, and this study did not have a control group 6 .…”
Section: Introductionmentioning
confidence: 99%